2022
DOI: 10.1111/anae.15884
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes after prenatal exposure to anaesthesia for maternal surgery: a propensity‐score weighted bidirectional cohort study

Abstract: Up to 1% of pregnant women undergo anaesthesia for non-obstetric surgery. This study investigated neurodevelopmental outcomes after prenatal anaesthesia for maternal surgery. A bidirectional cohort study of children born between 2001 and 2018 was performed: neurodevelopmental outcomes of children who had received prenatal anaesthesia for maternal surgery were prospectively compared with unexposed children, with exposure status being assessed retrospectively. Children exposed to anaesthesia for obstetric and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…Unfortunately, clinical evidence was somewhat little. A recent clinical study indicated that prenatal anesthesia exposure for non-obstetric surgery may not result in clinically significant neurodevelopmental outcomes abnormalities . The subjective psychosocial problem questionnaires assess, effects of surgery, and underlying pathology may be closely related to this result.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, clinical evidence was somewhat little. A recent clinical study indicated that prenatal anesthesia exposure for non-obstetric surgery may not result in clinically significant neurodevelopmental outcomes abnormalities . The subjective psychosocial problem questionnaires assess, effects of surgery, and underlying pathology may be closely related to this result.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Anaesthesia, showed an increased risk with general anaesthesia, intraabdominal, laparoscopic or prolonged (> 1 h) surgery for executive function alone, with estimates for the weighted mean difference of t-scores in these subgroups ranging from 3.2 to 4.5, an effect size explained by the authors as being of similar magnitude to a parental university level education [8].…”
mentioning
confidence: 85%
“…The findings were similar with alternative statistical methodology including propensity score adjustment and matching, and in sensitivity analyses with age strata, or after exclusion of fetuses exposed to important confounders such as chemo‐ or radiotherapy and illicit drugs. Exploratory analyses showed an increased risk with general anaesthesia, intra‐abdominal, laparoscopic or prolonged (> 1 h) surgery for executive function alone, with estimates for the weighted mean difference of t‐scores in these subgroups ranging from 3.2 to 4.5, an effect size explained by the authors as being of a similar magnitude to a parental university level education [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the effect values for anesthesia are even smaller than those for other factors such as demographics (25). It is not difficult to understand how a child's good postnatal upbringing may offset a single, small exposure to prenatal anesthesia.…”
Section: Other Factors a Ecting Neurodevelopment In O Springmentioning
confidence: 99%